KOLABORASI SUMBER DAYA MANUSIA DALAM PENCAPAIAN TARGET DAN SASARAN KINERJA PEGAWAI UNTUK KETAHANAN PANGAN PADA DINAS TANAMAN PANGAN DAN HORTIKULTURA - Wulandari, Putri; Rahayu, Heffi Christya; Dewi, Ratna (Jurnal Daya Saing, 2025)
This research analyzes the collaboration of human resources at the Department of Food Crops and Horticulture in Rokan Hulu Regency to achieve food security. Although the agricultural sector has potential, indicators of food security, such as local food production, are not yet optimal. A qualitative method was employed to collect data through observations, interviews, and documentation. The findings indicate that positive collaboration is fostered through open communication and active interaction among the Head of the Department, staff, and farmers. Supporting factors for collaboration include effective communication, mutual trust, aligned goals, and good leadership. However, obstacles such as ineffective communication, cultural differences, and a lack of trust hinder collaboration. Continuous training for human resources in the Department is crucial to enhance skills and strengthen collaboration. Keywords: Collaboration, Human Resources, Food Security, Department of Food Crops, Rokan Hulu